(untitled) (International Journal of Nursing Care, 2020)
Decubitus ulcer commonly known as Bed sore or Pressure ulcer is one of the commonest cause of skin and tissue disruptions 1 . So here arises a need to create awareness regarding prevention of bed sores through education of student nurses to reduce the burden of bed sores. The study was undertaken to assess the knowledge regarding prevention of bed sores among B.Sc Nursing 1st year students and develop and implement a structured teaching programme in Army College of Nursing, Jalandhar cantt. The objectives of the study were to assess the pre – test knowledge scores, develop and implement structured teaching programme, to assess the post-test knowledge scores and to compare the pre – test and post- test knowledge scores. The pre experimental study was conducted on 40 selected subjects of B.Sc Nursing 1st year students, Army College of Nursing, Jalandhar cantt, Punjab. Data was collected by self structured questionnaire. The results indicated that the overall pre – test mean was 18.32 with the Standard deviation of 2.09 whereas the overall post –test mean knowledge score was 21.42 with the Standard deviation of 1.62 with the significant mean diffence of 3.1. Effectiveness of structured teaching programme was determined by Paired- t test. Value of t was found to be 5.58 which was greater than value of t0.05 at 39 degree of freedom that is 2.023.